Beyond the bipolar: allowing satisfaction and dissatisfaction to coexist - Souders, Dustin J.; Yu, Yixiu (Frontiers in Psychology, 2025)
This paper advances a separable, multi-dimensional account of satisfaction and dissatisfaction, proposing that they are distinct constructs that can coexist, particularly in contexts involving ambivalence and indifference. When we specify measurement, we operationalize this account with bivariate unipolar items (separate single-ended scales for both satisfaction and dissatisfaction) rather than a single unidimensional bipolar continuum. Drawing upon theories from psychology—including Herzberg’s Two-Factor Theory, Watson and Tellegen’s Circumplex Model of Affect, Cacioppo’s Evaluative Space Model, and Reinforcement Sensitivity Theory—we argue that positive and negative emotions are processed separately in the human mind, allowing for the simultaneous experience of satisfaction and dissatisfaction, rather than placing them on two ends of a single bipolar spectrum. By reviewing evidence from psychological sciences, information science, human-computer interaction, and other disciplines, we highlight the limitations of bipolar scales in capturing the complexity of human emotional states and the full range of human experience. We review qualitative and empirical evidence demonstrating that satisfaction and dissatisfaction arise from different factors and have unique influences on behavior and decision-making. Recognizing them as separate constructs allows for more accurate measurement and better understanding of phenomena involving ambivalence and indifference. We offer practical guidance for researchers on when to use bivariate unipolar versus bipolar scales, how to identify contextual factors contributing to satisfaction and dissatisfaction, and how to design measurement tools that capture the nuances of these constructs. Through this narrative literature review, we embrace the idea that a separable, multidimensional perspective facilitates a more complete understanding of human emotions, motivations, and behaviors, leading to deeper insights and more effective strategies.